Հնագույն սիմվոլների դրսևորումները հայոց հարսանեկան ծեսում - Մարիաննա Տիգրանյան (ՀՀ ԳԱԱ հրատ.)
В армянском свадебном обряде дню венчания предшествовал обряд восхваления «хны», который сопровождался специальными хвалебными песнями, плясками под звуки зурны и дhола. Хной невесте красили волосы, ладони, а жениху и крестному– мизинцы. According to ancient Armenian wedding traditions, the evening preceding the marriage ceremony ‘bridal henna night’, celebrations with ceremonial songs, dance-songs accompanied by dhole and zurna took place. Henna was applied to the hair and hand palms of the bride as well as to the baby finger of both the groom and the godfather.
Keywords: Ethnography; The family; Marriage; Woman; Manners and customs; Social Sciences